Selected Drivers of Education Quality : Pre- and In-Service Teacher Training - Independent Evaluation Group (World Bank, Washington, DC, 2020)
This evaluation examines how the World Bank has supported two types of professional development to improve teacher capacity—preservice and in-service training—and identifies how these drivers of education quality can be better designed, implemented, and scaled up.